Can Ketogenic Diet Improve Alzheimer's Disease? Association With Anxiety, Depression, and Glutamate System - de la Rubia Ortí, Jose Enrique; Fernández, David; Platero, Félix; García-Pardo, María Pilar (Frontiers in Nutrition, 2021)
Alzheimer’s disease is characterized by presenting an aged brain, which is linked to neuropsychiatric symptoms such as anxiety and depression that worsen quality of life and disease course. This aging process, is mediated in turn at a central level, by the presence of β amyloid plaques and by alterations in the synaptic and extrasynaptic activity of the neurotransmitter glutamate, which are linked events to a hypometabolism of the glucose as the main source of cerebral energy. In this sense, pharmacologic treatments of these symptoms seem to be counterproductive, worsening the disease prognosis. This is why the alternative of consuming ketogenic diets as a mitochondrial energy source is raised and discussed, since they could improve that hypometabolism by acting both at the synaptic level: improving the glutamate synapsis glutamate in the NMDA synaptic receptors (sNMDAR), blocking the toxicity resulting from the formation of amyloid plaques after the activation of mGluR2 / 3 glutamate receptors, and enhancing glutamate function as a consequence of a greater ATP contribution which favours cognitive and emotional capacity; and extrasynaptic: since ketone bodies act as glutamate inhibitors in the NMDA extrasynaptic receptor (eNMDAR) decreasing inflammation, added to the characteristic neuroprotector effect of these metabolites precisely because they better the electron chain functioning which leads to a lower oxidative stress and inflammation.